Pemanfaatan Limbah Kotoran Dan Urine Sapi Perah Sebagai Penghasil Energi Alternatif Dan Pupuk Organik - Al Haris, Muhammad Fuad; Hidayat Kusuma, Dedy; Rahimi Bachtiar, Riza (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Kaligondo Village is an area that is a center for Small and Medium Enterprises (SMEs) engaged in the dairy farming sector in Genteng District, Banyuwangi. Where many people work as dairy farmers starting in 2001. The increasing need for fresh milk in the Banyuwangi area and the partnership between dairy farmers in Kaligondo Village and the national dairy company "Nestle" since 2012 has formed the Sumber Lumintu Livestock Farmers Group with 15 members. There are 32 female breeders with FH (Friesian Holstein) dairy cows that can produce ±400 liters of fresh milk per day. The waste generated is ± 800 kg per day. Manure waste management is generally only piled up and left alone in the yard or placed in dug holes so that the yard or cowshed looks dirty, spreads unpleasant odors, and can be a source of disease to the surrounding environment. Through this service activity, the implementing team implemented the use of cow dung to produce low-cost biogas using balloon digester. The utilization of cow dung waste shows a large enough potential for the availability of biogas to help empower the Sumber Lumintu Livestock Farmer Group, especially the need for fuel so that the financial savings made can be allocated for other economic interests. Slurry biogas can also be used as an organic fertilizer to replace chemical fertilizers